Accuracy of endoscopic ultrasonography in diagnosing ascites and predicting peritoneal metastases in gastric cancer patients. Issue 11 (13th June 2005) - Lee, Y T; Ng, E K W; Hung, L C T; Chung, S C S; Ching, J Y L; Chan, W Y; Chu, W C; Sung, J J
Abstract : Background: Preoperative diagnosis of peritoneal metastases (PM) is difficult in patients with gastric cancer (GC). Aims: To assess the accuracy of endoscopic ultrasonography (EUS) in diagnosing ascites and its predictability for the presence of PM in GC patients. Subjects: Consecutive patients with newly diagnosed GC from 1998 to 2004 were studied. Methods: All patients underwent EUS, ultrasound (US), and computed tomography (CT) scan for preoperative staging and the presence of ascites. The results were compared with operative findings. The diagnosis of PM was confirmed by histopathology or peritoneal fluid cytology. Results: A total of 301 patients were recruited and in 250 patients the presence of ascites (n = 93) and PM (n = 71) were confirmed. EUS was more sensitive (87.1%) than combined US and CT scan examinations (16.1%) and operative findings (laparoscopy or laparotomy) (40.9%) in diagnosing ascites. Sensitivity, specificity, positive and negative predictive values, and accuracy for predicting the presence of PM were 73%, 84%, 64%, 89%, and 81% by EUS; 18%, 99%, 87%, 75%, and 76% by combining US and CT scan; and 77%, 94%, 83%, 91%, and 89% by operative findings, respectively. In multivariate logistic regression analysis, EUS detected ascites was the only significant independent predictor for the presence of PM (p<0.001; odds ratio 4.7 (95% confidence interval 2.0–11.2)). Conclusion: EUS is a sensitive method for diagnosing ascites which is an important predictive factor for the presence of PM in GC patients.